Validasi Model Numerik Spektrum Gelombang Menggunakan Data Wave Recorder Platform Minyak & Gas Lepas Pantai - Defriyantoro, Gatot; Radityo, Samuel; Supriyadi, Eko; Alfahmi, Furqon; Darma Putra, Ngurah Made (Jurnal Pendidikan Matematika : Judika Education, 2025)
Accurate ocean wave forecasting plays a pivotal role in navigational safety, maritime resource management, and offshore oil and gas operations, particularly within the Makassar Strait, which exhibits complex hydrodynamic dynamics. This study aims to evaluate the performance of the InaWave numerical model integrated into the BMKG Ocean Forecasting System through validation against in-situ observation data from a wave recorder positioned on the FPU Jangkrik offshore platform throughout 2023. The results indicate that the InaWave model effectively captures the fluctuation patterns of Significant Wave Height (SWH) with a strong correlation coefficient of 0.88, demonstrating a robust linear relationship between simulations and observations. However, the model exhibits a systematic underestimation bias, specifically during high-wave conditions, with a Root Mean Square Error (RMSE) of 0.36 meters. The error distribution, centered near zero, suggests high accuracy under low-to-moderate wave conditions, yet highlights the necessity for refinement in capturing extreme dynamics. Overall, this research underscores that integrating in-situ observational data from offshore platforms is a critical instrument for enhancing the precision of ocean forecasting systems. The successful reconstruction of wave patterns by the InaWave model confirms its operational reliability for complex maritime environments. These findings not only provide a scientific foundation for strengthening Indonesia’s maritime early warning systems but also offer an applicable validation framework for numerical model development in other strategic global waters to mitigate operational risks and ensure marine ecosystem sustainability.   Keywords: InaWave Model, Numerical Model Validation, X-Band Wave Radar, Significant Wave Height, Makassar Strait.